Improving Confirmation System Models for Data Security in Distributed Cloud Computing: A Review: Enhancing Data Security in Distributed Cloud Computing Systems (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is environment which enables convenient, efficient, on-demand network access to a shared pool of configurable computing resources (e.g., networks, servers, storage, applications, and services) that can be quickly provisioned and released with insignificant management exertion or service provider cooperation.Cloud computing is a globalized idea and there are no boundaries inside the cloud. Computers used to process and store user data can be found anyplace on the globe, depending on where the capacities that are required are accessible in the worldwide computer networks utilized for cloud computing. Due to the alluring highlights of cloud computing numerous organizations are utilizing cloud storage for putting away their basic information. The data can be stored remotely in the cloud by the users and can be gotten to utilizing slight clients as and when required. One of the significant issue in cloud today is data security in cloud computing. Storage of data in the cloud can be hazardous in light of utilization of Internet by cloud based services which implies less control over the stored data. One of the significant worry in cloud is how would we snatch all the advantages of the cloud while keeping up security controls over the organizations assets. Our point is to propose a more solid, decentralized light weight key management technique for cloud systems which gives more proficient data security and key management in cloud systems. Our proposed system models gives better security against byzantine failure, worker plotting and data alteration attacks.